Study for quality and amount of carbonic acids in the leaves of Urtica dioica L. - G. P. Smoilovska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2015)
Search and elaboration of plant-based drugs which stimulate physiological functions of organism are key trend of current scientific researches.